المشعرات المخبرية الموجهة لحدوث ماقبل الارتعاج الحملي اثناء ارتفاع الضغط الحملي - عبد الله أنسام (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: preeclampsia is one of the most common and most serious complications of pregnancy , it is characterized by an unexpected start and development which is the second leading cause of maternal mortality. Aim: determination of the most sensitive laboratory probabilities of high pressure hypertension Material and methods:a prospective study was conducted on 100 patients with high pressure pregnancy tests for the university obstetric hospital during the whole year. The patients data were taken on a research form and 3 types of tubes were withdrawn (dry, edta, citrate) with a random or randomized urine sample. Blood tests were performed (creatine, urea,ast ,alt ,cbc ,pt ,ptt) and urine tests were micro albumin urea. The results were distributed in tables and evaluated in a statistical way by calculating the mean and standard deviation and drawing the roc curve to determine the cut off Value for the micro albumin urea test Resuts: MAU test was satisfactory ( more than 15 mg/dl) in 92% of gestational hypertensive patients who did not develop preeclampsia and were satisfactory in 100% of patients who developed preeclampsia , the value of MAU and its elevation was an indicator of developing preeclampsia In our study (cr ,urea ,ast ,alt ,cbc, pt ,ptt) tests did not provide any benefit to predict the development of preeclampsia and did not change etheir development Conclusion: the MAU test should be performed for each pregnancy with any risk factors to develop pregnancy pressure and repeat the analysis because MAU value were indicators of the development of the condition. The study shows the futility of conducting (cr ,urea ,ast ,alt ,pt ,ptt ,cbc ) to detect preeclampsia but may be conducted to monitor preeclampsia patients who are likely to develop eclampsia and did not need to repeat their request in the absence of satisfactory values. المقدمة: يعتبر من أشيع وأخطر الاختلاطات في الحمل ويتميز ببدء وتطوير غير متوقع حيث يعتبر ثاني أسباب الوفيات الوالدية يؤدي إلى المراضة الجنينية. هدف البحث: تحديد المشعرات المخبرية الأكثر حساسية لتبدلات ارتفاع الضغط الحملي. المواد والطرق: أجريت دراسة مستقبلية على 100 مريضة ارتفاع ضغط حملي, المراجعات لمشفى التوليد الجامعي خلال عام كامل . تم أخذ بيانات المريضة على استمارة خاصة بالبحث وسحب 3 أنواع من الأنابيب Edta ,جاف ,سيترات مع أخذ عينة بول صباحية أو عشوائية مشروطة. تم اجراء الفحوص الدموية : كرياتين , بولة PLT ,PT,ALT,AST,CBC , فحوص بولية : إجراء اختبار البيلة الالبومينية الدقيقة MAU و تكرر المراقبة للمريضة مرة ئاخرى و تسجل كافة النتائج على استمارة المريضة و تم توزيع النتائج ضمن جداول و تقييمها بطريقة إحصائية عن طريق حساب المتوسط الحسابي و الانحراف المعياري و رسم منحنى roc لتحديد قيمة Cut off بالنسبة لاختبار البيلة الالبومينية الدقيقة. ملخص النتائج : كانت قيمة MAU مرضية <) 15 ملغ / دل ) عند 92% من مريضات ارتفاع الضغط الحملي اللواتي لم يطوروا ما قبل الارتعاج و مرضية عند 100% من المريضات اللواتي طوروا ارتعاج و ما قبل ارتعاج وكانت قيمة MAU و درجة ارتفاعها مؤشر لتطور ما قبل الارتعاج الحملي. و من خلال دراستنا لم تقدم قيم الخضاب و وظائف الكلية و خمائر الكبد و اختبارات التخثر اي فائدة للتنبؤ بتطور ما قبل الارتعاج الحملي و لم تبدي تغير لهم عند تطوره. الخلاصة : يجب اجراء اختبار MAU لكل حامل لديها اي عامل من عوامل الخطورة لتطوير ارتفاع الضغط الحملي وتكرر التحليل لان قيم MAU كانت مؤشر لتطور الحالة و من الدراسة تبين عدم جدوى أجراء البولة و الكرياتين و خمائر الكبد و اختبارات التخثر للكشف عن ما قبل الارتعاج الحملي و إنما يمكن اجرائها لمراقبة مريضات ما قبل الارتعاج اللواتي لديهن احتمال تطوير ارتعاج ولا داعي لتكرار طلبها في حال عدم وجود قيم مرضية.